ROLE OF NIDANA PANCHAKA IN VARIOUS AYURVEDIC ASPECTS (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda, the Indian system of medicine, has its own branch of specialty for understanding the disease process and proper diagnosis of a disease. Caraka has stated that the diagnosis is very important and essential before proceeding to medicine prescription. Ayurvedic way of diagnosis has 2 basic components namely Rogapariksha and Rogipariksha, which refers to Examination of disease and Examination of patient respectively. Among them Rogapariksha gives us the detailed knowledge about a disease starting from the etiological aspects to the actual manifestation of disease. The five basic components of Rogapariksha are Nidana, Purvarupa, Rupa, Upasaya and Samprapti, which are collectively known as Nidana Panchaka. Apart from diagnosing a disease, they also play a key role in planning the treatment of that disease. Nidana, the foremost component of Nidana Panchaka, not only gives the knowledge of causative factors of a disease but also helps in treatment by avoiding them. Purvarupa refers to Premonitory signs & symptoms and represents the 4th stage of disease formation. If physician is able recognize them as early as possible and treat accordingly, then the further progression of disease is ceased. In the same way, every component of Nidana Panchaka helps the physician for the better understanding of disease process and treating the disease at an earliest possible stage. The details of Nidana Panchaka and its role in diagnosis & treatment are explained elaborately in full paper.